Nanotechnology Activities in Thailand: Present and Future Perspectives - TANTHAPANICHAKOON, Wiwut; CHAIKITTISILP, Watcharop (Journal of Metals, Materials and Minerals, 2022)
The current situations of nanotechnology in the advanced industrial countries, the USA, the European Union, and Japan, are introduced to cast contrasting light on the recent development and promotion of nanotechnology in Thailand, especially the recent establishment and planned roles of the National Nanotechnology Center. A brief overview of the current situation and future perspectives of Nanotechnology in Thailand is given from the authors’ view.